Agreement between qSOFA and NEWS scores in the screening of sepsis through Monte Carlo simulation - Mendes, Miguel Damásio Cardoso; Kock, Kelser de Souza (Revista Prevenção de Infecção e Saúde, 2023)
Introduction: The early warning scores used for sepsis have different risk stratification and accuracy metrics, which can delay diagnosis by the health team. Aim: The study aims to evaluate the agreement and differences between the qSOFA and NEWS criteria in the early detection of sepsis risk in a defined population through a computer simulation. Outlining: A computer simulation was performed using the Monte Carlo method. 10,000 cases were simulated based on the variables described by the NEWS and qSOFA scores. Results: After evaluating the 10,000 cases, qSOFA≥2 proved to be less sensitive (22.22% (95% CI 21.00 – 23.49)) than NEWS≥7 (93.41% (95% CI 91.72 – 94.78)). When analyzing specificity, NEWS≥7 (62.99% (CI 95% 61.98 – 63.98)) was lower than qSOFA≥2 (98.83% (CI 95% 98.52 – 99.08)). Agreement was 66.08% (95% CI 65.15 - 67.00). Implications: The study showed good agreement between the scores and also showed that NEWS is superior to qSOFA when analyzing sensitivity, but the result is reversed when talking about specificity.